Impact of BRACTS exercises on muscular strength in eumenorrheic women - Wajiha Shahid; Rabiya Noor (Scientific Reports)
Abstract The sex steroid hormones significantly impact women’s physiology. Therefore, recently developed integrated exercises consisting of Bending, Roll-ups, Arm swings with loads, Crunches, Tandem walks, and Squats (BRACTS) were formulated. It was the exercise approach that required minimal equipment and was cost-effective and practical for implementation across a broad spectrum of women. So, this study aims to evaluate the effects of BRACTS exercises on strength during different phases of the menstrual cycle in eumenorrheic women. This is a two-armed parallel design, single-blinded, randomized controlled trial following Consolidated Standards of Reporting Trials (CONSORT) guidelines, and the study protocol is based on Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guidelines. Participants were randomly allocated with a 1:1 ratio into Group A (control group) and Group B (treatment group). Group A was given an educational program related to menstrual hygiene and active lifestyle maintenance with 20 min walk 3 times a week for 16 weeks, while group B was given an educational program related to menstrual hygiene along with BRACTS exercises of 50 min for 3 times per week for 16 weeks. Assessments were done at baseline, midline, and end of the therapy using SPSS version 25. The experimental group demonstrated a notable improvement in muscular strength in follicular, mid-cycle, and luteal phases, with Cohen’s d values for left and right hand grip strength to be maximum in follicular phase while for left and right quadriceps, left and gastro-soleus showed maximum Cohen’s d value in mid-cycle phase of menstrual cycle. The mixed model ANOVA indicates statistically significant differences (p < 0.05) between the two groups, with influence from menstrual cycle phases. So, the BRACTS exercise protocol significantly improves muscular strength across different phases of the menstrual cycle in eumenorrheic women, demonstrating its efficacy as a cost-effective and practical approach. The trial was registered on clinicaltrials.gov for registration with ID: NCT05460741 on 05/31/2022 and was last released on 04/29/2024. Trial registration number: NCT05460741.